Effect of Elastic Bandage Wraps on Leg Edema in Patients before and after Liver Transplant. (December 2015) - Mathews, Susan; James, Shantell; Anderson, Janet D.; Merchant, Mehwish; Benenati, Sonia; Henry, Samantha; Comrie, Gem; Pirani, Shamsa; Zellinger, Mary
Context—: Few studies have evaluated the benefits of short-term use of compression therapy to prevent or minimize edema and/or pain in the legs of acutely ill, hospitalized patients without venous leg ulcers. Objective—: To determine if the use of elastic bandage wraps of the leg in patients before and after liver transplant decreases edema formation and pain in the leg. Study Population—: A convenience sample of inpatients before and after liver transplant. Study Design—: Pretest, posttest, randomized controlled trial with each participant serving as his or her own control. Intervention—: Elastic bandage wrap applied to leg for 8 hours. Outcome Measures—: Edema and pain in leg. Results—: In 13 patients before and 11 patients after liver transplant, the mean (SD) change in leg circumference after a single 8-hour application of an elastic bandage wrap was −2.6 (2.2) cm at the ankle and −3.1 (2.9) cm at midcalf for wrapped legs, as opposed to −0.4 (1.6) cm at the ankle and 1.0 (2.8) cm at midcalf for unwrapped legs ( P < .001). Leg pain, measured on a visual analog scale, was significantly lower for the wrapped (mean [SD], 10.3 [26.5] mm) versus the unwrapped (20.3 [33.5] mm) leg ( P = .04). Conclusion—: In inpatients before and after liver transplant, the application of elastic bandage wraps to 1 leg for an 8-hour period led to significantly less edema formation and pain compared with the unwrapped leg. These results support the use of elastic bandage wraps in liver transplant patients to reduce leg edema and improve comfort.